Keputusan Pembelian Helm: Analisis Pengaruh Harga, Kelompok Acuan, dan Persepsi Risiko - Masrifah Masrifah; Didit Darmawan (PPIMAN Pusat Publikasi Ilmu Manajemen, 2023)
This study aims to analyse the impact of price, reference group, and risk perception on purchasing decisions for KYT brand helmets in Surabaya. Quantitative methods were used by distributing questionnaires to 100 purposively selected KYT helmet consumers. The results showed that the price of KYT helmets has a significant effect on purchasing decisions, and the propensity to purchase increases when the price is considered commensurate with the quality of the product. The role of reference groups also proved important, influencing consumer preferences in choosing KYT helmets. In addition, purchase decisions are influenced by perceived risk, where consumers who are confident in the safety and quality of the product are more likely to purchase. The practical implications of these findings help helmet manufacturers and marketers in Surabaya design more effective marketing strategies. This research can also serve as a basis for further research on helmet market dynamics and consumer behaviour in Surabaya.